The determinants of inflation rate in Malaysia (1984-2014) / Norkhalilah Ariff Fadzillah - Ariff Fadzillah, Norkhalilah (Faculty of Business and Management, 2016)
The aim of this study is to investigate the relationship between Inflation Rate with macroeconomic variables or indicator as an independent variable that would be affect to the dependent variables. The researchers has investigated how those of the variables would effect on the inflation rate specially in Malaysian economy by using yearly basis data from year 1984 to 2014. There have three variables that have been taken to be as independent variables of this study. The name of the chosen variables is money supply, interest rate and exchange rate. The researcher interested study in the relationship between inflation and macroeconomic variables mostly used tools to indicate the change trends in the economy.